Prospective evaluation of regional oxygen saturation to estimate central venous saturation in sepsis - Koch, Christian; Röhrig, Rainer; Monz, Tobias; Hecker, Andreas; Uhle, Florian; Schneck, Emmanuel; Weigand, Markus A.; Lichtenstern, Christoph (Journal of clinical monitoring and computing, 2015)
Current treatment guidelines for sepsis claim an early goal-directed hemodynamic optimization including fluid resuscitation, use of vasopressors and inotropic agents. We investigated the correlation between the prominent treatment goal central venous saturation (ScvO2) and the frontal and the thenar regional oxygen saturation (rSO2) measured by near infrared spectroscopy. Secondary, we examined the value of ScvO2, lactate levels and rSO2 as surrogate markers of an impaired tissue oxygenation for outcome prediction in sepsis.
Gesehen am 14.07.2020